Pengembangan Bahan Ajar Bahasa Melayu Jambi Berbasis Saintifik - Akhyaruddin Akhyaruddin; Agus Setyonegoro; Hilman Yusra; Oky Akbar (Ranah: Jurnal Kajian Bahasa, 2023)
This research aims to develop scienitific-based Jambi Malay language teaching material product. The method used to achieve the objektives is Research and Development (R&D) with Analysis, Design, Development, Implementation, and Evaluation procedures. To find out the teaching material product use, the researcher use validition questionnaire method of material experts, scientific experts, language experts, graphics experts. Questionnaeres were also distributed to students as users of teaching material products to find out the practicality of teaching material products, which include: material, language, graphics and ease of use. All data obtained through questionnaires were processed with descriptive statistics. Using Likert scale criteria, expert validation results show that the material aspect of teaching materials has a percentage of 84,44% with a very valid category; the scientific aspect obtained a percentage of 92% with a very valid category; the language aspect obtained  a percentage of 96% with a very valid category; the graphic aspect obtained a percentage of 90% with a very valid category. Based on the results of user practitioner test, material feasibility wa sobtained at 95%. Thus, the resulting Jambi Malay language teaching material products are suitable for implementation in the lecture process. AbstrakPenelitian ini bertujuan mengembangkan produk bahan ajar bahasa Melayu Jambi berbasis saintifik. Metode yang digunakan untuk mencapai tujuan adalah Research and Development dengan prosedur Analysis, Design, Development, Implementation, and Evaluation. Untuk mengetahui kelayakan produk bahan ajar yang dikembangkan digunakan metode angket validasi ahli ahli materi, ahli saintifik, ahli bahasa, dan ahli grafika. Angket juga disebarkan kepada mahasiswa sebagai pengguna produk bahan ajar untuk mengetahui kepraktisan produk bahan ajar yang meliputi: materi, bahasa, grafika, dan kemudahan pengguna. Keseluruhan data yang diperoleh melalui angket diolah dengan statistik deskriptif. Dengan menggunakan kriteria skala likert, hasil validasi ahli menunjukkan bahwa aspek materi bahan ajar memiliki persentase 84,44% dengan kategori sangat valid; aspek saintifik memperoleh persentase 92% dengan kategori sangat valid; aspek bahasa memperoleh persentase 96% dengan kategori sangat valid; aspek grafika memperoleh persentase 90% dengan kategori sangat valid. Berdasarkan hasil uji praktisi pengguna, diperoleh kelayakan produk buku bahan ajar sebesar 95% dengan kategori sangat layak. Dengan demikian, produk bahan ajar bahasa Melayu Jambi yang dihasilkan layak diimplementasikan dalam proses pembelajaran.